2017
DOI: 10.1039/c7ay00641a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of eleven estrogenic and odorous chloro- and bromo-phenolic compounds in surface water through an automated online headspace SPME followed by on-fiber derivatization coupled with GC-MS

Abstract: HS-SPME followed by on-fiber derivatization coupled with GC-MS is developed for simultaneous determination of eleven estrogenic chloro- and bromo-phenolic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…analysis needs a derivatization procedure for hydroxyl functional groups. The most commonly used derivatization reagents are TMS reagents containing N-methyl-N-(trimethylsilyl)trifluoroacetamide), N-methyl-N-tertbutyldimethylsilyl-trifluoroacetamide, BSTFA and TMCS for derivatization of polyphenolic compounds and their metabolites (25,28,34,35). TMS reagents are hydrolyzed in aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…analysis needs a derivatization procedure for hydroxyl functional groups. The most commonly used derivatization reagents are TMS reagents containing N-methyl-N-(trimethylsilyl)trifluoroacetamide), N-methyl-N-tertbutyldimethylsilyl-trifluoroacetamide, BSTFA and TMCS for derivatization of polyphenolic compounds and their metabolites (25,28,34,35). TMS reagents are hydrolyzed in aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…For the convenience of comparison, relative activity is used, and the maximal enzyme activity is arbitrarily set to 100%. The limit of detection (LOD) of the spectrophotometric method was calculated according to three times of the standard deviation, which was obtained from nine repeated determinations of the lowest p NP concentration used for the standard calibration curve. , The LOD of this method for p NP was 0.22 μM, which is equal to 0.22 U/L for arylsulfatase and β-glucuronidase.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of chlorophenols in water is very important due to its high toxicity level ( Gallego et al, 2018 ). Many studies had reported the extraction of chlorophenols and some estrogenic compounds using HS-SPME, followed by on-fiber derivatization coupled with GC-MS ( Yuan et al, 2017 ).…”
Section: Applicationsmentioning
confidence: 99%